Formation of competitive advantages of the enterprise - Posokhov, I. M.; Pererva, P. G.; Lepskyi, R. S. (My University, 2023)
The report proves that the marketing strategy is also always connected with the problems that are solved when choosing a successful enterprise in the future. In difficult market conditions, the enterprise must develop fundamentally new methods of solving all emerging management, marketing, financial and other problems.
Формування конкурентних переваг підприємства
Keywords: market; production; competitive advantages; demand; consumers; enterprises